Long-term changes in cardiovascular risk markers during administration of exenatide twice daily or glimepiride: results from the European exenatide study - Simó, Rafael; Guerci, Bruno; Schernthaner, Guntram; Gallwitz, Baptist; Rosas-Guzmàn, Juan; Dotta, Francesco; Festa, Andreas; Zhou, Ming; Kiljański, Jacek (Cardiovascular diabetology, 2015)
Objective The risk of cardiovascular morbidity and mortality is significantly increased in patients with diabetes; thus, it is important to determine whether glucose-lowering therapy affects this risk over time. Changes in cardiovascular risk markers were examined in patients with type 2 diabetes treated with exenatide twice daily (a glucagon-like peptide-1 receptor agonist) or glimepiride (a sulfonylurea) added to metformin in the EURopean EXenAtide (EUREXA) study. Research design and methods Patients with type 2 diabetes failing metformin were randomized to add-on exenatide twice daily (n = 515) or glimepiride (n = 514) until treatment failure defined by hemoglobin A1C. Anthropomorphic measures, blood pressure (BP), heart rate, lipids, and high-sensitivity C-reactive protein (hsCRP) over time were evaluated. Results Over 36 months, twice-daily exenatide was associated with improved body weight (−3.9 kg), waist circumference (−3.6 cm), systolic/diastolic BP (−2.5/−2.6 mmHg), high-density lipoprotein (HDL)-cholesterol (0.05 mmol/L), triglycerides (−0.2 mmol/L), and hsCRP (−1.7 mg/L). Heart rate did not increase (−0.3 beats/minute), and low-density lipoprotein-cholesterol (0.2 mmol/L) and total cholesterol (0.1 mmol/L) increased slightly. Between-group differences were significantly in favor of exenatide for body weight ( P < 0.0001), waist circumference ( P < 0.001), systolic BP ( P < 0.001), diastolic BP ( P = 0.023), HDL-cholesterol ( P = 0.001), and hsCRP ( P = 0.004). Fewer patients randomized to exenatide twice daily versus glimepiride required the addition of at least one antihypertensive (20.4 vs 26.4 %; P = 0.026) or lipid-lowering medication (8.4 vs 12.8 %; P = 0.025). Conclusions Add-on exenatide twice daily was associated with significant, sustained improvement in several cardiovascular risk markers in patients with type 2 diabetes versus glimepiride. Clinical trial registration: NCT00359762, http://www.ClinicalTrials.gov